2011
DOI: 10.3390/sym3020265
|View full text |Cite
|
Sign up to set email alerts
|

Prolinethioamides versus Prolinamides in Organocatalyzed Aldol Reactions—A Comparative Study

Abstract: Various organocatalysts have been developed for the aldol reaction but particular attention has been paid to prolinamide derivatives. They are easy to prepare and their catalytic activity can be readily tuned through structural modification. In this review, the comparison of catalytic activities between prolinethioamides and their respective amides in direct asymmetric aldol reactions is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 62 publications
0
5
0
1
Order By: Relevance
“…The conversion of amide moiety to the corresponding thioamide [216] increases the acidity of amide and therefore allows the formation of stronger hydrogen bonds. Thioamide 157 (20 mol%) was evaluated in the intermolecular aldol reaction between acetone (52a, 27.2 equiv) and aromatic aldehydes at 4 • C in the presence of TFA (20 mol%) affording the expected compounds 54 in good results (20-86%, 73-94%).…”
Section: Proline Derivatives As Organocatalysts 189mentioning
confidence: 99%
“…The conversion of amide moiety to the corresponding thioamide [216] increases the acidity of amide and therefore allows the formation of stronger hydrogen bonds. Thioamide 157 (20 mol%) was evaluated in the intermolecular aldol reaction between acetone (52a, 27.2 equiv) and aromatic aldehydes at 4 • C in the presence of TFA (20 mol%) affording the expected compounds 54 in good results (20-86%, 73-94%).…”
Section: Proline Derivatives As Organocatalysts 189mentioning
confidence: 99%
“…On performing glycosylation using catalyst 3 d , afforded the product 14 & 15 with comparable yields and selectivity (62–66%, α:β 10:1–11:1). Whereas in case of catalyst 3 e & 3 f , a drastic change in the yield of the product 14 was observed that manifest the importance of substituted NH 2 of catalyst 3 b towards its reactivity [29] …”
Section: Resultsmentioning
confidence: 96%
“…Whereas in case of catalyst 3 e & 3 f, a drastic change in the yield of the product 14 was observed that manifest the importance of substituted NH 2 of catalyst 3 b towards its reactivity. [29] Scheme 4. Synthesis of trehalose-type 1,1'-linked sugars.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, the amide derivatives are a useful class of these types of catalysts. Because they can be synthesized easily, they contain NH group to make hydrogen bond with aldehyde to activate it, and their structures can be modified to change their catalytic activity [7].…”
Section: Introductionmentioning
confidence: 99%